1989
DOI: 10.1177/107110078901000106
|View full text |Cite
|
Sign up to set email alerts
|

Stabilizing Effect of the Tibiocalcaneal Fascicle of the Deltoid Ligament on Hindfoot Joint Movements: An Experimental Study

Abstract: The tibiocalcaneal fascicle of the deltoid ligament was studied in 10 lower leg amputation specimens to evaluate its stabilizing effect on movement in the tibiotalocalcaneal joint complex and the talocalcaneal joint complex. Cutting of the fascicle resulted in minor numerical increases in movement in all three planes in the tibiotalocalcaneal joint complex as well as in the talocalcaneal joint complex. The maximum median increase in the tibiotalocalcaneal joint complex was 6.1 degrees in abduction, whereas the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 20 publications
1
13
0
Order By: Relevance
“…Previous studies have evaluated biomechanics 1) by using a laboratory reference axis system to obtain a three-plane description of movements [13], 2) after sectioning each ligamentous band [7], 3) by using reluctance transducers to measure change in the deltoid ligament length [16], 4) by using computational models [18], and 5) by using a marker-based motion analysis [19]. This is the first study in which each ligamentous band of the deltoid was investigated without transection; thus, we precisely assessed how each ligament works.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have evaluated biomechanics 1) by using a laboratory reference axis system to obtain a three-plane description of movements [13], 2) after sectioning each ligamentous band [7], 3) by using reluctance transducers to measure change in the deltoid ligament length [16], 4) by using computational models [18], and 5) by using a marker-based motion analysis [19]. This is the first study in which each ligamentous band of the deltoid was investigated without transection; thus, we precisely assessed how each ligament works.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have evaluated biomechanics by 1) using a laboratory reference axis system to obtain a three-plane description of movements [13], 2) after sectioning of each ligamentous band [7], 3) by using reluctance transducers to measure deltoid ligament length change [16], 4) by using computational models [18], and 5) a marker-based motion analysis [19]. This is the first study in which each ligamentous band of the deltoid has been investigated without transection.…”
Section: Discussionmentioning
confidence: 99%
“…10 The only study conducted under axial load was that of Hintermann et al 5 who demonstrated increased calcaneal eversion under a static load. No clinical studies have discussed the relationship of deltoid injury to subtalar joint instability, probably because isolated deltoid injury is rare.…”
Section: Discussionmentioning
confidence: 99%
“…In laboratory experiments, disruption of the lateral ligaments has been associated with increased calcaneal adduction, 9,11 increased eversion, 5 increased inversion, 26 increased internal rotation, 17 increased supination, 21 increased anterior translation, 6,9 and no observable change in calcaneal position. 8,9 Deltoid ligament injury has been reported to lead to increased calcaneal eversion, 19,29 increased external rotation, 10,17,21 increased pronation, 21 increased plantarflexion, 10,21 and increased abduction. 10 The diversity of results is primarily a result of differing experimental methods (loading of the specimens, static or dynamic testing conditions, characteristics of the external stress applied) and measurement techniques (radiographic, direct).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation